Diversity and metabolic potential of culturable marine actinomycetes from the sediment of Amundsen Sea, Antarctica - Lee, Jeonghee; Silviani, Velina; Kang, Soojin; Choi, Hyukjae; Yang, Inho (Frontiers in Marine Science, 2025)
The Antarctic marine environment is a promising region for the discovery of extraordinary microbial taxa and the exploration of their applications. This study aimed to investigate the phylogenetic diversity of culturable actinomycetes from deep sea bottom sediment of the Amundsen Sea, Antarctica, and their potential to produce novel metabolites. A total of 24 actinomycete strains were isolated and assigned to the following genera based on the 16S rRNA gene sequence analysis: Blastococcus (3 strains), Corynebacterium (2 strains), Microbacterium (3 strains), Micrococcus (1 strain), Modestobacter (3 strains), Nocardioides (3 strains), Rhodococcus (6 stains), and Streptomyces (3 strains). The 15 strains were selected and chemically investigated. A molecular networking analysis was performed using tandem mass spectrometry (MS/MS) to analyze the metabolites produced by 15 strains. This analysis was used to annotate known compounds and identify potential novel compounds. The molecular network that resulted from this analysis contained 3,702 parent ions. Of these, 1,414 parent ions (38.20%) were identified as genus-specific compounds. Feature-based molecular networking analysis revealed the presence of 269 annotated compounds within the GNPS library. This study demonstrates the diversity of the marine actinomycetes isolated from Amundsen Sea sediment. Additionally, the molecular networking analysis suggests the capacity for the production of biologically active compounds.